Analysis of the expression and significance of lymphocyte ratio in different stages and clinical types of COVID-19: Lymphocyte in COVID-19 - Xu, Jinwei; Yao, Guangyao; Zhang, Aili; Gao, Haixiang; Yan, Li (Cellular and Molecular Biology, 2023)
This study aimed to analyze the expression of lymphocyte ratio (LY%) in different stages and clinical staging of COVID-19 and explore the relationship between peripheral blood lymphocyte (PBL) ratio and COVID-19 severity to provide reference for early intervention. For this purpose, a total of 125 patients with COVID-19 admitted to Hebei Provincial People’s Hospital from February 1, 2020, to March 1, 2022, were reviewed and divided into moderate, severe, and critical groups by the severity to analyze and compare peripheral lymphocyte ratios of patients with different clinical typing. Results showed that lymphocyte count, lymphocyte percentage, CD3+ T-lymphocyte count, CD4+ T-lymphocyte count, and CD8+ T-lymphocyte count all decreased gradually with increasing severity (F = 27.84, P<0.05; F = 15.28, P<0.05; F = 46.12, P<0.05; F = 34.65, P<0.05); the absolute numbers of CD3+, CD4+ and CD8+ cells in peripheral blood were higher in the recovery phase than in the acute phase (P<0.05). In conclusion, COVID-19 may cause a decrease in the number of lymphocytes, and the decrease in the number of lymphocytes and T-lymphocyte subsets may predict the severity of the disease. The fewer lymphocytes there are, the more likely they are to progress to the severe type and the worse the prognosis.